Right Accessory Renal Artery: Anatomical, Clinical and Surgical Importance – A Cadaveric Case Report - Smitaraje D Wader; Ramesh Killedar; M B Ramannavar; Pradeep S. Shindhe (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Background: Renal artery variations are common anatomical findings, occurring in approximately 23% of kidneys. They are reported more frequently in males (30%) than females (11%), and are more common on the right side (60%) than the left (26%), while bilateral variations account for approximately 11% of cases. Accessory renal arteries most commonly supply the superior pole (41.7%), followed by the hilar region (29.2%) and inferior pole (29.2%). Case Presentation: During routine cadaveric dissection in the Department of Rachana Sharira, KAHER's Shri BMK Ayurved Mahavidyalaya, Shahapur, Belagavi, a variation in the right renal arterial anatomy was observed. The cadaver exhibited a right accessory renal artery in addition to the main renal artery. Morphometric measurements were obtained using a standard ruler for length and a Vernier caliper for arterial diameter, and the findings were systematically documented. Findings: A right accessory renal artery measuring 6.5 cm in length and 3 mm in diameter originated from the abdominal aorta just superior and slightly to the left of the origin of the main right renal artery. The accessory artery supplied the right suprarenal gland and the inferior pole of the right kidney. Conclusion: Recognition of a right accessory renal artery is clinically important because such vascular variations may influence renal transplantation, nephrectomy, vascular reconstruction, and other retroperitoneal surgical procedures. Awareness of these anatomical variations facilitates accurate preoperative planning and helps reduce the risk of inadvertent vascular injury and associated surgical complications.